2012
DOI: 10.3329/icpj.v1i10.11849
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of UV spectroscopic methods for simultaneous estimation of ciprofloxacin and tinidazole in tablet formulation

Abstract: Two simple, accurate, precise, reproducible and economical UV spectroscopic methods (A &  B) for simultaneous estimation of Ciprofloxacin and Tinidazole in tablet dosage form have been developed. Method A employs solving of simultaneous equations based on the measurement of absorbance at two wavelengths, 271nm and 318nm which are the ?max values of Ciprofloxacin and Tinidazole respectively in phosphate buffer (pH 6.8). Method B is based on the principle of  Q-Analysis where in the absorbance was measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Ciprofloxacin (ciproxine 500, Bayer Schering Pharma) was dissolved in water, sterile-filtered, and the concentration was quantified by UV spectrometry (A 271 nm  = 30,614 l×mol −1 ×cm −1 ; [59]). It was applied intragastrically twice daily, as indicated (2×62 mg/kg per day).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ciprofloxacin (ciproxine 500, Bayer Schering Pharma) was dissolved in water, sterile-filtered, and the concentration was quantified by UV spectrometry (A 271 nm  = 30,614 l×mol −1 ×cm −1 ; [59]). It was applied intragastrically twice daily, as indicated (2×62 mg/kg per day).…”
Section: Methodsmentioning
confidence: 99%
“…B6-Tg(Itgax-EYFP) mice expressing EYFP under the CD11c promoter (CD11c-YFP; [26] ), CD11c-DTRtg heterozygous transgenic mice (B6.FVB-Tg(Itgax-DTR/EGFP)57Lan/J; CD11c-DTR tg ; [30] ), CX 3 CR1 gfp/+ heterozygous transgenic mice (CX 3 CR 1 tm1Litt ) [27] , TLR4 −/− (TLR4 lps-del ) mice [58] , and wild-type C57BL/6 mice were bred and kept specified pathogen free in individually ventilated cages (RCHCI, ETH Zürich). Ciprofloxacin (ciproxine 500, Bayer Schering Pharma) was dissolved in water, sterile-filtered, and the concentration was quantified by UV spectrometry (A 271 nm = 30,614 l×mol −1 ×cm −1 ; [59] ). It was applied intragastrically twice daily, as indicated (2×62 mg/kg per day).…”
Section: Methodsmentioning
confidence: 99%
“…All standard and sample solutions absorbance was measured at 261nm and 255nm with their respective blanks. 4,5 Method B: Absorbance Ratio Method/ Q-Analysis The absorbance ratio method is a modification of thesimultaneous equation procedure. It depends on theproperty that for a substance, which obeys Beer's lawat all wavelength, the ratio of absorbance at any twowavelengths is constant value independent ofconcentration or path length.…”
Section: Methodsmentioning
confidence: 99%
“…When distilled water was used as the solvent, the average percentages of potency measured by UV-Spectrophotometer and HPLC were 97.64±0.78% and 98.76±0.55%, respectively ( Table 3). Though methods using UV spectrophotometry have been already reported for the determination of ciprofloxacin 19,20 , the method on study showed satisfactory results using distilled water, the cheapest reagent. Previously, it was reported that the reaction rate of thermal decomposition of ciprofloxacin HCl increased at 30, 40, 50, 60 and 70ºC when the temperature rises up 25 .…”
Section: Fig1: Calibration Curve Of Ciprofloxacin Hclin the Media Ofmentioning
confidence: 96%
“…The UV spectrophotometric analysis is often preferred in quality control testing and ordinary laboratories as it is simple, easy, less time consuming and an economical method 17,18 . Though methods using UV spectrophotometry have been already reported for the determination of ciprofloxacin 19,20 , these methods require expensive reagents, involve tedious extraction steps or need time for the reaction between the analyte and the colorimetric reagent.…”
Section: Introductionmentioning
confidence: 99%